Exploring the Relationship Between Demographic Factors and Consumers’ Buying Behaviour Towards Cause - Based Marketing: An Assessment Study - Gupta, Shruti; Chaudhry, Harish; Kamal, Harsh (Indian Journal of Marketing, 2015)
Cause - related marketing has been gaining strength for the last two decades not only in the Western world, but across the globe. Since its advent in the USA, it has been growing continuously in Europe and other developed countries as well. This marketing strategy is slowly penetrating into the markets of developing countries and has the potential to become a driving force in the field of social marketing. Companies cannot hope to succeed in another country simply by applying the successful model of a different country. Corporations need to have country-specific data of consumers’ opinions so that they can come up with appropriate marketing strategies. Since the contribution to the cause is directly related to the sales and profit, consumers can sometimes be sceptic about the companies’ motives behind these strategies or choose to support them too. However, at the end, these strategies are extremely crucial in creating a pragmatic approach in luring the customers’ choice in an extremely competitive environment. Using a survey method, the paper attempted at evaluating customers’ opinion regarding cause - related marketing by analyzing three measures: perception of customers, image of a company, and intention of customers when purchasing CRM products.